Central Asia's Transition after Fifteen Years: Growth and Policy Choices - DOWLING, Malcolm (Institutional Knowledge at Singapore Management University, 2006)
This paper presents a coherent and systematic analysis of the collapse and subsequent revival of the Central Asian Republics (CARs) since 1990. The focus is on the pattern of growth and structural change during the cycle of decline and subsequent revival in the CARs which have been inadequately analyzed in the literature on transition. The paper relates economic performance to initial conditions, country characteristics and policies. Within this framework, it proposes a simple typology of policies (including a new Type III set of policies on regional cooperation and industrial competitiveness) and relates them to the cycle of decline and revival in the CARs. It goes on to examine medium-term prospects and policy needs for the CARs.